2020
DOI: 10.1124/jpet.119.264192
|View full text |Cite
|
Sign up to set email alerts
|

Pre-eclamptic Fetal Programming Alters Neuroinflammatory and Cardiovascular Consequences of Endotoxemia in Sex-Specific Manners

Abstract: Pre-eclampsia (PE)-induced fetal programming predisposes offspring to health hazards in adult life. Here, we tested the hypothesis that pre-eclamptic fetal programming elicits sexually dimorphic inflammatory and cardiovascular complications to endotoxemia in adult rat offspring. PE was induced by oral administration of L-NAME (50 mg/kg per day for seven consecutive days) starting from day 14 of conception. Cardiovascular studies were performed in conscious adult male and female offspring preinstrumented with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 78 publications
6
18
0
Order By: Relevance
“…A number of studies have shown that a similar effect of L-NAME is observed at higher doses [25][26][27]. Consistent with previous research [38], blood pressure elevation was observed in L-NAME-treated females despite a compensatory decrease in heart rate, which suggests an increase in peripheral vascular resistance. Importantly, peripheral vasoconstriction upon L-NAME treatment may be due to the inhibition of not only vascular eNOS [39], but also the nNOS of brain stem neurons responsible for cardiovascular control [3].…”
Section: L-name Treatment Leads To No Deficiency In Dams and Their Offspringsupporting
confidence: 86%
“…A number of studies have shown that a similar effect of L-NAME is observed at higher doses [25][26][27]. Consistent with previous research [38], blood pressure elevation was observed in L-NAME-treated females despite a compensatory decrease in heart rate, which suggests an increase in peripheral vascular resistance. Importantly, peripheral vasoconstriction upon L-NAME treatment may be due to the inhibition of not only vascular eNOS [39], but also the nNOS of brain stem neurons responsible for cardiovascular control [3].…”
Section: L-name Treatment Leads To No Deficiency In Dams and Their Offspringsupporting
confidence: 86%
“…For example, in patients with preserved ejection fraction, this is a plausible mechanism leading to cardiomyocyte hypertrophy [46]. In addition, in a rat model of fetal programming induced by preeclampsia, myocardial inflammatory pathways have been described in males, but not in females [47]. 21-day old MUN males exhibited a normal ejection fraction, but diastolic dysfunction together with hypertrophy and fibrosis, and we have previously demonstrated that males, but not females, exhibit increased plasma oxidative damage biomarkers [12] and elevated cardiac NADPH oxidase expression [13].…”
Section: Discussionmentioning
confidence: 99%
“…First, ADMA competes with Larginine to inhibit NO production [68] and its increase is involved in coronary artery disease [69], congenital heart disease [70], type 2 diabetes [71], stroke [72], obesity [73], and peripheral arterial occlusive disease [74]. Second, gestational NO depletion induced by N G -nitro-L-arginine-methyl ester (L-NAME, an inhibitor of NOS) causes cardiovascular programming in adult offspring, characterized as endothelial dysfunction, hypertension, defect of carotid artery, and cardiac hypotrophy [75,76]. Third, reprogramming effects of therapeutic strategies targeting the ADMA/NO pathway to prevent the developmental programming of hypertension have been reported in various animal models [76][77][78][79].…”
Section: No Deficiencymentioning
confidence: 99%